Decadal Predictions of the Probability of Occurrence for Warm Summer Temperature Extremes. Issue 23 (10th December 2019) - Borchert, Leonard F.; Pohlmann, Holger; Baehr, Johanna; Neddermann, Nele‐Charlotte; Suarez‐Gutierrez, Laura; Müller, Wolfgang A.
Abstract: We use a decadal prediction system with the Coupled Model Intercomparison Project Phase 6 version of the coupled Max Planck Institute Earth System Model to predict the probability of occurrence for extremely warm summers in the Northern Hemisphere. An assimilation run with Max Planck Institute Earth System Model shows a robust response of summer temperature extremes in northern Europe and northeast Asia to North Atlantic sea surface temperature via a circumglobal Rossby wavetrain. When the North Atlantic is warm, warm summer temperature extremes occur with a probability of 20 % and 24 % in northern Europe and northeast Asia, respectively. In a cold North Atlantic phase, these probabilities are 0 % and 8 % . A similar difference in probability of occurrence is found in the initialized climate predictions. Consequently, the likelihood of a warm summer temperature extreme occurring in the examined regions in the next 10 years can be inferred from predictions of North Atlantic temperature. Plain Language Summary: Extremely warm summers can have a substantial impact on society. Trustworthy predictions of such events several years ahead could help in anticipating the extremes and managing their impacts. In this study, we show that the probability with which a warm summer temperature extreme occurs in northern Europe and northeast Asia can be linked to the surface temperature of the North Atlantic ocean. We further show that North Atlantic ocean surface temperature and the connection between ocean temperature and extreme summer temperature can be predicted. As a result, the probability for extremely warm summers to occur in northern Europe and northeast Asia in the next 10 years can be predicted. Key Points: Extremely warm summers in northern Europe and northeast Asia occur more frequently when the North Atlantic is warm than when it is cold A set of initialized CMIP6 decadal hindcasts predicts this dependence of summer temperature extremes on North Atlantic temperature The likelihood of extremely warm summers to occur in the next 10 years can be inferred from predictions of North Atlantic ocean temperature